Is CT Angiogram of the Abdominal Vessels Needed following the Diagnosis of Ischemic Colitis? A Multicenter Community Study. (12th February 2014) - Sherid, Muhammed; Samo, Salih; Sulaiman, Samian; Husein, Husein; Sethuraman, Sankara N.; Vainder, John A.
Abstract : Background . CT angiogram is frequently obtained after diagnosis of ischemic colitis (IC). Aims . To investigate the vascular findings of CT angiogram as compared to contrast-enhanced CT scan and whether this modality changes the management or prognosis of IC. Methods . We conducted a retrospective analysis of patients with IC from 2007 to 2013. Results . CT angiogram was performed in 34 patients (28.81%), whereas contrast-enhanced CT scan was performed in 54 patients (45.76%). In CT angiogram group, 8 patients (23.5%) had atherosclerotic changes. Stenosis was found in 12 patients (35.3%) (9: celiac trunk, 3: SMA). Among this group, one patient underwent colectomy and another underwent angioplasty of the celiac trunk who died within 30 days. Among contrast-enhanced CT scan group, 5 patients (9.3%) had atherosclerotic changes. Stenosis was found in 5 patients (9.3%) (3: celiac trunk, 1: SMA, and 1: IMA). Among this group, 3 patients had colectomy and one died within 30 days. There was no statistical difference between both groups in all vascular findings except the stenosis which was higher in CT angiogram group (P = 0.0025 ). Neither the need for surgery nor all-cause mortality was different between both groups. Conclusion . CT angiogram did not provide any useful findings that altered the management or the prognosis of IC.